A Comparative Study Between Fentanyl and Lignocaine on Attenuation of Hemodynamic Response to Laryngoscopy and Intubation in Cardiac Patients - Khan, Namra; Khan, Abid; Malik, Usman Eijaz; Rizvi, Ali Mazhar; Saqib, Najm us; Ameer, Khalid (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate and compare the efficacy of intravenous low-dose fentanyl versus lignocaine in mitigating the occurrence of hemodynamic response during endotracheal intubation.Study Design: Quasi –experimental study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Feb to Jul 2023.Methodology: The study included 82 patients, aged between 30 and 65 years, undergoing elective non-cardiac surgery requiring general anesthesia and randomized them into two groups to compare the effects of intravenous Lignocaine (Group L) and Fentanyl (Group F) before laryngoscopy, on patients with moderate lower ventricular dysfunction (left ventricular ejection fraction between 35- 45%). All patients had mean arterial pressure (MAP) and pulse rate recorded during laryngoscopy and intubation.Results: The baseline pulse rate in Group F was 73.76±4.90 beats per minute, increasing to 84.53±6.32 during laryngoscopy and intubation while baseline MAP was 91.85±1.93 mm of Hg which increased to 95.55±4.09 mm. However, in Group L, the heart rate escalated substantially upon laryngoscopy and intubation and increased to 91.78±1.84 beats per minute from baseline heart rate of 72.85±4.95 beats per minute, while MAP during laryngoscopy and intubation increased to 106.57±4.401 mm of Hg from 91.78±1.84mm of Hg (p-value